Sistem Informasi Pendataan Pelayanan Kesehatan Penderita Diabetes Mellitus Menggunakan Metode Online Analytical Processing (OLAP) - Mochammad Januar Finandi; Fauziah Fauziah; Ira Diana Sholihati (STMIK Budi Darma, 2023)
In the era of globalisation, the impact is felt in various fields, including the epidemiology of infectious diseases, which has decreased, and non-communicable diseases (NCDs), which have increased. One of the most prevalent NCDs is diabetes, with a prevalence of 1.74% in the population aged 15 years and over, according to a doctor's diagnosis. According to the Depok City Health Office, diabetes is among the top 10 non-communicable diseases. The number of diabetes patients in all health centres in Depok is around 27,000 people. With this background, it is important to develop an application using online analytical processing (OLAP) techniques that displays data from each sub-district in Depok City. This application helps to retrieve data and information on how to prevent and manage diabetes, as well as provide useful information for diabetes patients. Based on the test results, the application accuracy is 80.85% when tested using the Web Application Penetration Testing (WAPT) method, and the average time required to retrieve service data is 0.030168182 seconds, and the average time required to retrieve patient data using the sequential search method is 0.025498182 seconds